STRICT LIABILITY IN ENVIRONMENTAL CIVIL DISPUTES IN INDONESIA - Junaedi (Program Magister Ilmu Hukum, STIH Painan, 2022)
Current legal rules are needed in order to realize Indonesia as a country based on law. One of the legal concepts adopted from the Anglo Saxon legal system is the concept of absolute liability. The concept of absolute liability (strict liability) is a form of civil responsibility that does not require an element of fault, but only requires an element of loss as a condition for submitting a claim for compensation for an unlawful act. The principle of absolute responsibility in enforcing civil environmental law in Indonesia has been regulated in the provisions of Law No. 4 of 1982 concerning Basic Provisions for Environmental Management and Article 88 of Law Number 32 of 2009 concerning Environmental Protection and Management. those responsible for activities (potential polluters) will pay attention to their level of care in carrying out their activities. This article was written with the approach used, namely the approach of using statutory regulations (statute approach) and conceptual (conceptual approach) to obtain a strong legal basis to then be confronted with existing concepts and theories so as to produce an in-depth and comprehensive analysis of Strict Liability in Environmental Civil Disputes in Indonesia.